Extinct species identification from late middle Pleistocene and earlier Upper Pleistocene bone fragments and tools not recognizable from their osteomorphological study by an enhanced proteomics protocol. (7th July 2022) - Bray, Fabrice; Flament, Stéphanie; Abrams, Grégory; Bonjean, Dominique; Rolando, Christian; Tokarski, Caroline; Auguste, Patrick
Abstract: Ancient preserved molecules offer the opportunity of gaining a deeper knowledge on their biological past. However, the development of a proteomic workflow remains a challenge. The analysis of fossils must involve a low quantity of material to avoid damaging the samples. In this study an enhanced proteomic protocol was applied to 5‐milligram samples of about 130, 000‐year‐old mammalian bones ranging from the end of the Middle Pleistocene up to the earlier Upper Pleistocene, excavated from Scladina Cave (Sclayn, Belgium). Using sequence homology with modern sequences, a biological classification was successfully achieved and the associated taxonomic ranks to each bone were identified consistently with the information gained from osteomorphological studies and palaeoenvironmental and palaeodietary data. Amino acid substitutions on collagens were identified, thus providing new information on extinct species sequences and helping in taxonomy‐based clustering. Considering samples with no osteomorphological information, such as two fragments of bone retouchers, proteomics successfully identified the families providing paleontologists new information on these objects. Combining osteomorphology studies and amino acid variations identified by proteomics, one of the retouchers was potentially identified as belonging to the Ursus spelaeus species.